Real‐Time Multipoint Gastrointestinal 19‐Fluorine Catheter Tracking. Issue 1 (11th February 2013) - Hahn, Tobias; Kozerke, Sebastian; Schwizer, Werner; Fried, Michael; Boesiger, Peter; Steingoetter, Andreas
<x xml:space="preserve">Abstract</x> Purpose To develop MR based real‐time gastrointestinal 19‐Fluorine (19F) catheter tracking and visualization allowing for real‐time detection and feedback of 3D catheter shape and movement as well as catheter‐driven adjustments of 1H imaging geometry parameters. Methods Data were acquired on a 3T clinical system using 3D Golden Angle radial sampling. Two gastrointestinal catheters incorporating four fiducial 19F markers (65 or 50 µL marker volume) were tracked while being pulled through a gel phantom by an operator inside the MR room with velocities of 2–18 mm/s. During continuous acquisition, k‐space profiles were transferred in real‐time to an external computer for concurrent reconstruction of 3D 19F images and detection and visualization of marker positions. Based on αthe marker positions, automatic adjustments of 1H imaging planes to facilitate targeted anatomical scanning was implemented. Results Mean tracking reliabilities were 94.5 and 83.6% (catheters 1 and 2) for temporal resolutions 185–740 ms. Reconstruction times of 196 ms were achieved. Real‐time visual feedback allowed the operator to accurately control the catheter movement. Catheter‐guidance for 1H imaging was reliable. Conclusion The presented real‐time 19F MR based framework for the tracking of 19F labeled devices is applicable to combined 19F and 1H MRI guidance of gastrointestinal devices in vivo. Magn Reson Med 71:302–307, 2014. © 2013 Wiley Periodicals, Inc.